The Effect of Droplet Sizes on Overspray in Aerosol‐Jet Printing. Issue 8 (23rd April 2018) - Chen, Guang; Gu, Yuan; Tsang, Harvey; Hines, Daniel R.; Das, Siddhartha
Abstract : One of the most important concerns of aerosol‐jet based printing (AJP) is the substantial amount of overspray (OS) that can accompany printed traces. In this study, the authors develop a full, three‐dimensional (3‐D) computational fluid dynamics (CFD) model of the aerosol carrier gas flow (CGF), that is, confined by an annular sheath gas flow (ShGF) during the AJP process. The authors then use this model to pinpoint the fundamental fluid mechanics principles that control the OS in a standard AJP process as a function of the droplet size distribution and the ShGF rate. In their model, the authors consider the trajectories of various sized, monodisperse droplets in an ink‐stream in order to unravel the manner in which the OS is dictated by the intricate interplay between drop size and both gas flow (CGF and ShGF) rates. Their results explain several experimental results, namely 1) that there is an abundance of smaller sized drops in the OS region at low ShGF rates; 2) that the OS first reduces and then increases as the ShGF rate increases; and 3) that there is no longer a prevalence of smaller particles in the OS region at larger ShGF rates. The authors also discuss the hitherto unaddressed issues related to how 1) the large impact velocity of the ink droplets at the substrate surface (and the resultant Weber number) and 2) the misalignment between the CGF and the cylindrical axis of the ShGF annulus appear to affect OS. The authors anticipate that their analysis will provide an important understanding in the optimization of operating parameters for AJP with respect to OS that can result in an overall improvement in printing resolution. Abstract : A theory is developed to probe the overspray (OS) formation in Aerosol Jet 3D printing explaining the experimental findings of abundance of smaller sized drops in the OS region at low ShGF rates, non‐monotonic variation of OS with the ShGF rate, and a lack of prevalence of smaller particles in the OS region at larger ShGF rates.